What do our patients understand about their trial participation? Assessing patients' understanding of their informed consent consultation about randomised clinical trials. Issue 2 (23rd November 2010) - Behrendt, C; Gölz, T; Roesler, C; Bertz, H; Wünsch, A
Abstract : Background: Ethically, informed consent regarding randomised controlled trials (RCTs) should be understandable to patients. The patients can then give free consent or decline to participate in a RCT. Little is known about what patients really understand in consultations about RCTs. Methods: Cancer patients who were asked to participate in a randomised trial were surveyed using a semi-standardised interview developed by the authors. The interview addresses understanding, satisfaction and needs of the patients. The sample included eight patients who participated in a trial and two who declined. The data were analysed on the basis of Mayring's qualitative analysis. Results: Patients' understanding of informed consent was less developed than anticipated, especially concerning key elements such as randomisation, content and procedure of RCTs. Analysing the result about satisfaction of the patients, most of the patients described their consultations as hectic and without advance notice. Health limitations due to cancer played a decisive role. However, most of the patients perceived their physician to be sympathetic. Analysing the needs of patients, they ask for a clear informed consent consultation with enough time and adequate advance notice. Conclusion: This study fills an important empirical research gap of what is ethically demanded in an RCT consultation and what is really understood by patients. The qualitative approach enabled us to obtain new results about cancer patients' understanding of informed consent, to clarify patients' needs and to develop new ideas to optimise the informed consent.